Development And Characterization Of Normoxic Polyhydroxyethylacrylate (Nphea) Gel Dosimeters Using Magnetic Resonanc Imaging (Mri) Clinical Scanner - Haghiri, Maryam Erfani (2009)
Polymer gel dosimeter is a three dimensional (3D) polymer gel system for recording radiation dose distribution in radiotherapy treatment planning. The dosimeter is based on polymerization of copolymers induced locally by free radicals, the products of water radiolysis. Interaction of free radicals with the monomer and crosslinker causes a breakage of double C=C bonds into single C-C bonds, leading to copolymerization between the two copolymers to form high density insoluble polymer in gelatin matrix and is normally achieved by purging nitrogen into the system to remove oxygen during preparation. In this work, new type of polymer dosimeter, i.e. the ‘normoxic’ polymer gels, is synthesized by adding oxygen scavenger to remove oxygen. The dosimeter is based on polyhydroxyethylacrylate (nPHEA) gels containing 2-4% (w/w) 2-hydroxythylacrylate (HEA) monomer, 2-4% (w/w) bisacrylamide (BIS) comonomer, 3-5% (w/w) gelatin, and 87-93% (w/w) water in normal atmospheric condition. The polymer gel phantoms were irradiated with beam doses up to 30 Gy using 60Co teletherapy -ray source at a constant dose rate of 0.22 Gy/min. The polymerization of nPHEA dosimeters was evaluated by means of magnetic resonance imaging (MRI) clinical scanner, which produced 3D optical density distribution and registered as MRI films. The gray scale of MRI images was measured using an optical densitometer. The optical density of the polymer gels was found to increase with increasing of absorbed dose and decreased with the increase of depth inside the phantom. The optical density was then converted to absorb dose by a mathematical relationship obtained from the experiment. The dose-depth maps for nPHEA gels were obtained for different concentrations of co-monomers, gelatin and at different beam doses. The results indicated that dose decreases of with decreasing of depth and gelatin concentration and increases with increasing of co-monomer concentrations. Finally the cross beam dose-depth map has been acquired by irradiating nPHEA phantom from two (3 cm x 3 cm) square -ray beams of 14 Gy and 25 Gy which perpendicular to each other. The results showed the distribution of 3D dose-depth profile that decreased with increasing depth and lower beam dose. One region of high dose distribution in particular was seen in the overlapped beams, which in the actual clinical practices, it may represent a cancer volume that to be inactivated with higher dose than the surrounding healthy non-cancer tissues.